Understanding society : poverty, wealth and inequality in the UK - Morelli, Carlo J.; Seaman, Paul T. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This poignant book examines poverty, wealth and inequality in the UK, and provides insight into its history, its present-day forms and possible routes to its eradication. This book is an excellent resource for students, policy makers and lecturers seeking a greater understanding of poverty, wealth and inequality in the UK. It will be of particular interest to those working in or studying the fields of human geography, economics and social policy"--
Introduction: Understanding Society: Poverty, wealth and inequality in the UK -- Understanding Society: Subjectivity, datasets and methodological aproaches -- Extreme Poverty: A structural inequality? -- The top 10%: Income and Wealth Inequality -- Inequality and Devolution. Localised solutions to poverty and inequality -- Child Poverty: creating intergenerational poverty -- Conclusion: An evidence-based policy agenda for ending poverty.
OCLC-licensed vendor bibliographic record.
Keywords: Poverty -- Great Britain; Equality -- Great Britain; Great Britain -- Economic conditions -- 21st century; Great Britain -- Social conditions -- 21st century; POLITICAL SCIENCE / Public Policy / Social Policy; SOCIAL SCIENCE / Sociology / General